Core elements of informationization-based enterprises evaluation system of power industry - Bingqiang GAO; Yu ZHANG (Dianxin kexue)
After more than ten years of development and construction,the electric power industry has achieved remarkable results.Information integration of the company's production,operation and management of various fields,strongly promote the transformation of development of the company and power production.Informatization has become the key driving force to promote the production of electric power safety,customer service,scheduling and control,and gradually realize the transformation of enterprise information to the information enterprise.Based on the current situation of electric power enterprise information construction,the core elements of the evaluation system of the electric power industry informatization enterprise were studied,and the framework of information enterprise evaluation system was put forward.